Synthesis of RNA containing inosine: analysis of the sequence requirements for the 5' splice site of the Tetrahymena group I intron. - Green, R (1991)
Two protected derivatives of the ribonucleoside inosine have been prepared to serve as building blocks for phosphoramidite-based synthesis of RNA. Two different synthetic routes address the unusual solubility characteristics of inosine and its derivatives. The final products of the different synthetic pathways, 5'-O-(dimethoxytrityl)-2'-O-(t-butyldimethylsiyl) inosine 3'-O-(beta-cyanoethyldiisopropylamino) phosphoramidite 5a, and O6-p-nitrophenylethyl-5'-O-(dimethoxytrityl)-2'-O-(t-butyldimethylsilyl) inosine 3'-O-(methyldiisopropylamino) phosphoramidite 5b, were chemically incorporated into short oligoribonucleotides which also contained the four standard ribonucleoside bases. The oligomers were chosen to study base-specific interactions between an RNA substrate and an RNA enzyme derived from the Group I Tetrahymena self-splicing intron. The oligomers were shown to be biochemically competent using a trans cleavage assay with the modified Tetrahymena intron. The results confirm the dependence of the catalytic activity on a wobble base pair, rather than a Watson-Crick base pair, in the helix at the 5'-splice site. Furthermore, comparison of guanosine and inosine in a wobble base pair allows one to assess the importance of the guanine 2-amino group for biological activity. The preparation of the inosine phosphoramidites adds to the repertoire of base analogues available for the study of RNA catalysis and RNA-protein interactions.